An Ethnographic Study of the Concept of COVID-19 in the Belu Community Beliefs - Djulianus Tes Mau; Maria Julieta Esperanca Naibili (Universitas Aisyah Pringsewu, 2022)
The spread of COVID-19 that has swept across the world as a global public health emergency is an unexpected, sudden, unplanned, and unimaginable event that has even affected the world in all aspects of the fabric of people's lives including psychological, economic, educational and social. culture. Belu is one of the districts in East Nusa Tenggara Province, Indonesia. The main style of culture in the Belu Regency is that it has four major ethnic groups, namely Tetun, Marae, Kemak, and Dawan which are thick with customs by the teachings of the Belu tradition. The Belu community has a view of life that believes that there is a close relationship between individuals, society, and nature which is symbolized through various forms in the form of traditions of carrying out ritual or customary ceremonies. To explore public perception about the concept of COVID-19 in public trust in Belu Regency, East Nusa Tenggara Province. Methods An ethnographic approach used by focused ethnography. Data Collection for 6 months (May until October) through interviews, documents, and observations. Tested semi-structured interview guide. The type of purposive sampling consisted of 14 participants consisting of 4 communities, 6 health workers, and 4 traditional elders living in Belu. Data analysis using NVIVO. Analysis of qualitative ethnographic research data using the Spradley Model to look for cultural themes, found three main themes: (1) Other Names or Local Designations for COVID-19 (2) Community Trust vs Mistrust against the Danger of COVID-19 (3) Standing, Blocking, Expelling, Deterring and Fencing and Unite in Dealing with COVID-19. Abstrak: Penyebaran COVID-19 yang melanda di seluruh dunia sebagai darurat kesehatan masyarakat global merupakan suatu peristiwa yang tidak terduga, tiba-tiba, tanpa perencanaan dan tak terbayangkan bahkan telah mempengaruhi dunia pada segala aspek tatanan kehidupan masyarakat mencakup psikologis, ekonomi, pendidikan dan sosial budaya. Belu merupakan salah satu kabupaten di Provinsi Nusa Tenggara Timur, Indonesia. Corak utama kebudayaan di Kabupaten Belu yaitu memiliki empat etnis besar yaitu Tetun, Marae, Kemak, dan Dawan yang kental dengan adat sesuai dengan ajaran tradisi Belu. Masyarakat Belu memiliki pandangan hidup yang meyakini bahwa terdapat hubungan erat antar individu, masyarakat, dan alam yang dilambangkan melalui berbagai bentuk berupa tradisi melaksanakan upacara-upacara ritual atau adat. Mengeksplorasi persepsi masyarakat tentang konsep COVID-19 dalam kepercayaan masyarakat di Kabupaten Belu, Provinsi Nusa Tenggara Timur. Metode penelitian etnografi menggunakan focused ethnography. Data dikumpulkan selama 6 bulan (Mei s.d. Oktober) melalui wawancara, dokumen, dan observasi. Wawancara semi struktur menggunakan pedoman wawancara. Tipe Purposive Sampling tediri dari 14 partisipan mencakup 4 orang masyarakat, 6 orang tenaga kesehatan, 4 orang tua adat. Analisis data menggunakan NVIVO. Analisis data penelitian kualitatif etnografi menggunakan Model Spradley untuk mencari tema-tema budaya, ditemukan tiga tema utama : (1) Nama Lain atau Sebutan Lokal untuk COVID-19 (2) Trust vs Mistrust Masyarakat terhadap Bahaya COVID-19 (3) Berdiri, Menghadang, Mengusir, Menangkal dan Memagar serta Bersatu dalam Menangani COVID-19.